Tennissense: a multi-sensory approach to performance analysis in tennis - Conroy, L.; O'Conaire, C.; Kelly, P.; Coyle, S.; Nixon, P.; Healy, G.; Connaghan, D.; O'Connor, N.; Caulfield, B.; Smeton A. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
There is sufficient evidence in the current literature that the ability to accurately capture and model the accelerations, angular velocities and orientations involved in the tennis stroke could facilitate a major step forward in the application of biomechanics to tennis coaching (Tanabe & Ito, 2007; Gordon & Dapena, 2006). The TennisSense Project, run in collaboration with Tennis Ireland, aims to create the infrastructure required to digitally capture physical, tactical and physiological data from tennis players in order to assist in their coaching and improve performance. This study examined the potential for using Wireless Inertial Monitoring Units (WIMUs) to model the biomechanical aspects of the tennis stroke and for developing coaching tools that utilise this information.